The wet nurses of the Hospital Real of Santiago de Compostela between 1803 and 1808 - Campos Villar, Carla; Pego Pérez, Emilio Rubén (Investigación y Educación en Enfermería, 2024)
Objective. To analyze the duties of wet nurses at the Hospital Real in Santiago de Compostela (Spain). The secondary objectives were to compare the mortality rate and distribution by parish of the foundlings under the care of the Royal House between 1803 and 1808; and to determine the origin of the Galician foundlings who participated in the Royal Philanthropic Expedition of the Smallpox Vaccine in 1803. Methods. Historiographic study that analyzed sorted and not sorted in series indirect positional and quantitative historical sources. Results. The duties of wet nurses during the studied period were to provide basic care and cultural instruction. The mortality rate of foundlings fluctuated during that period and their distribution by parish (functional unit of healthcare services at that time) was similar in those years, with a predominance in the provinces of A Coruña and Pontevedra. A total of 5 Galician foundlings from the House analyzed were part of the smallpox vaccine expedition, their names were Juan Antonio, Jacinto, Gerónimo María, Francisco Florencio and Juan Francisco. Conclusion. During the observed period the wet nurses of the Hospital Real of Santiago de Compostela were in charge of pediatric care. Wet nurses were vital in the role of keeping the foundlings alive and can be considered as one of the forerunners of the pediatric nurse profession at that time.